The Impact of COVID-19 on Turkish Forest Products Industry - BAYRAM, Bahadır Çağrı (Bartin Orman Fakultesi Dergisi, 2021)
In the present paper the impact of COVID-19 pandemic on Turkish forest products industry was investigated with the help of quantitative research methods. Focus groups and interview methods were adopted as the methodology. The scope of the study is limited to wood-based panel, laminate flooring and furniture industries which are the leading branches within forest products industry of Turkey. The respondents are white-collar workers randomly chosen from engineers, managers or marketing directors of large-sized enterprises from Ankara and Bursa. The enterprises were limited with mentioned cities due to these cities are of great importance for the industry in management and marketing activities. Results showed that COVID-19 pandemic affected the labour force and income negatively. The key finding of this work is that if the pandemic lasts longer the substantial economic side effects will be inevitable. Also, the results suggest that at first the companies should focus on raw material supply and secondly to domestic market rather than the international market.
Keywords: 8. Economic growth; 15. Life on land; 3. Good health